Chronology and palaeoenvironmental reconstruction in the sub-tidal zone: a case study from Hinkley Point. (February 2015) - Griffiths, Seren; Sturt, Fraser; Dix, Justin K.; Gearey, Benjamin; Grant, Michael J.
Abstract: Evidence from the Severn Estuary demonstrates that this region was exploited by Mesolithic hunter-gatherer-fishers (Bell, 2007). The potential for future archaeological discoveries (Bell, 2007;Webster, 2007 : 273; Bell and Warren, 2013: 39), and the well-preserved palaeoenvironmental evidence in the fine-grained and organic sediments of the Somerset, Avon and Gwent Levels (Hosfield et al., 2007a : 40) makes the area of importance for archaeological study. Small quantities of worked flint have been recovered from the foreshore around Stolford, Porlock and Minehead Bay (Mullin et al., 2009 ; Canti et al., 1995) implying human activity in the present intertidal zone, which is further enhanced by the suggestion of possible deliberate burning of reed swamps (Jones et al., 2005 ) similar to that postulated in the Severn Estuary (Brown, 2005; Timpany, 2005 ; Bell, 2007). While considerable research has been carried out within terrestrial and intertidal contexts, remarkably little archaeological work has been undertaken below the mean low water mark (Webster, 2007 : 273). The Bristol Channel and Severn Estuary has seen considerable change in sea-level since the Last Glacial Maximum (Long et al., 2002; Philips and Crisp, 2010 ). Extending our knowledge beyond the intertidal zone is therefore of key importance for understanding the Late Palaeolithic and Mesolithic palaeogeography of the region (Hosfield et al., 2007b ). Developments in the recovery of offshore Holocene peat and sediment sequences now permit the production of multi-proxy palaeoenvironmental datasets and landscape reconstructions from submerged sample sites. This paper uses evidence from three cores, recovered from submarine peat deposits at Hinkley Point, Bristol Channel, UK, to explore the issues and challenges associated with producing radiocarbon chronologies from deeply submerged peat sequences within a marine environment. We emphasise the importance of analysis of multiple sequences to construct robust chronologies for local hydrological change and landscape reconstruction (Edwards, 2006 ). The need for local evidence is critical if we are to move beyond generalised and potentially misleading models of human–environment interaction (Scaife, 2011), because as this case study demonstrates, complex processes and landscape variability might have been features of even highly-localised palaeoenvironments. Highlights: Bayesian modelling of the chronology from a subtidal peat sample site. Importance of multiple-cores for landscape reconstruction and archaeological interpretation. For robust chronologies, critical consideration of radiocarbon samples is required. Consideration should include best practice examples from terrestrial wetland sites. Consideration should include potential specific marine and site effects on samples.